2014
DOI: 10.1039/c3cc47154c
|View full text |Cite
|
Sign up to set email alerts
|

A twisted bi-icosahedral Au25cluster enclosed by bulky arenethiolates

Abstract: Ligation of 2,6-diphenylbenzenethiol (DppSH) onto Au clusters stabilized by poly(N-vinyl-2-pyrrolidone) and subsequent core etching yielded a single cluster Au25(SDpp)11. High-energy X-ray diffraction measurement showed that Au25 constitutes a core in Au25(SDpp)11. We propose a bi-icosahedral Au25 core whose 22 Au surface atoms are capped directly by 11 bulky arenethiolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 22 publications
(21 reference statements)
1
43
0
1
Order By: Relevance
“…Pradeep and coworker used excess MSA ligands in toluene to etch (MSA-) protected large Ag nanoparticles into fluorescent Ag NCs [48]. Recently, some advances have been reported [49][50][51] to form more stable, monodisperse, and highly fluorescent AuNCs.…”
Section: Synthesis Fluorescence Qys Referencesmentioning
confidence: 99%
“…Pradeep and coworker used excess MSA ligands in toluene to etch (MSA-) protected large Ag nanoparticles into fluorescent Ag NCs [48]. Recently, some advances have been reported [49][50][51] to form more stable, monodisperse, and highly fluorescent AuNCs.…”
Section: Synthesis Fluorescence Qys Referencesmentioning
confidence: 99%
“…[97] In particular, core size of most stable clusters observed in solution, in general, does not correspond to "magic numbers" predicted for ligand-free gas phase clusters and it does not consider the effect of clusters ligands on clusters stability and properties. [57,60,61,98,99] These drawback have been partially overcome by more recent computational methods based on new approaches, including the "superatom complex", [22,100,101] the Super Valence Bond (SVB) [102][103][104][105][106] and the superatom- [101,107] models, that have been developed to describe clusters electronic structures, both in gas and in solution phase. [22,37,41,42,93,95,99,100,104,[108][109][110][111][112][113][114] …”
Section: Jellium and Related Modelsmentioning
confidence: 99%
“…Previous research has shown that the surface protecting ligands could have significant impacts on the structures and properties of the underlying metal nanoclusters . In this work, we are motivated to investigate the origin of photoluminescence of Au 36 (SR) 24 with different surface ligands via a ligand‐exchange process.…”
Section: Introductionmentioning
confidence: 99%